MODEL OF MOTORCYLCE OWNERSHIP AND ITS IMPACT TO URBANIZATION IN RURAL AREA: A CASE OF KUDUS REGENCY, INDONESIA - Sam'ani Intakoris; Sugiono Soetomo; Imam Buchori (Department of Urban and Regional Planning, Diponegoro University, 2018)
This paper aims to convey the fact that the use of motorcycles can have an impact on the urbanization process of rural communities. the study was conducted in Kudus by taking three villages namely Wonosoco, Padurenan, and Rahtawu. the data was processed using the average nierest neighborhood technique and hot spot analysis using GIS. The results show that motorcycle ownership forms a cusltered pattern with high intersection in all villages. These results show that motorcycles are the main drivers in rural economies. These findings reinforce the theory that motorcycles have a positive impact on rural growth, especially in developing countries.